Legal Reconstruction of Error in Persona Cases: Justice Enforcement Challenges Based on Due Process of Law Principle - Haniyah, Haniyah (Reformasi Hukum, 2024)
The case of misidentification of the perpetrators of the murder that occurred in Cirebon in 2016 involving Pegi Setiawan as a suspect reveals challenges in the investigation process and the enforcement of justice in Indonesia. This research aims to reconstruct the law regarding the phenomenon of error in persona and analyze the process of examining criminal cases related to wrongful arrest. The research method used is a normative approach with a statue approach,  a conceptual approach, and a case approach. This research involves the investigation process and case study of the murder of Vina Cirebon. The study results show that, in this case, law enforcement officials were unprofessional in identifying the perpetrator, which led to the wrong determination of the suspect. In addition, investigation procedures not by the law's provisions lead to human rights violations. These findings also show that law enforcement officials must pay more attention to the correct procedures to avoid harming innocent individuals. In conclusion, improvements in investigative mechanisms, forensic technology, and increased education and training for law enforcement are needed to prevent misidentification and fair law enforcement.